Analisis Plankton (Fitoplankton & Zooplankton) di Perairan Teluk Batu Kumbu Sekotong Barat - Bahri, Saipul; Sarjan, Muhammad (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Plankton are aquatic organisms that live floating with passive movement and cannot fight against the current. Plankton consists of phytoplankton and zooplankton. Given the very important role of plankton, research is needed. This study aims to analyze the condition of plankton (phytoplankton and zooplankton commodities) in the waters of Batu Kumbu Bay, Batu Kumbu Hamlet, West Sekotong Village, Sekotong District, West Lombok Regency. Water samples were taken using a plankton net and analyzed using a Sedgewick Rafter Cell (SRC) using a microscope. Data analysis in this study was in the form of the number of species, density (ind / L), dominance index, diversity index (H '), category, evenness and category. The results of this study showed the richness of phytoplankton species, it was found that the number of species found around coastal waters was relatively more, namely 37 species with a density of 159 individuals / liter. While around the jetty/pier there are 21 species with a species density of 91.3 while the richness of zooplankton species, it was found that the number of species found in the pier area, namely 2 species with a species density of 1 individual/liter and in the coastal area 3 species with a density of 2 individuals/liter. As for the level of species diversity (H') both phytoplankton and zooplankton in both locations, where the jetty tends to be low, while in coastal waters it is classified as moderate.